Impact of emotional style on academic goals in pandemic times - Garay, Jessica Paola Palacios (2020)
The objective of the present study was to determine the incidence of university students’ emotional style on the dimensions of academic goals (academic goals, learning goals, achievement goals and social reinforcement goals). For this study, 780 students of the fifth and sixth cycle of the Health Sciences School at a private university in Lima were chosen. In this quantitative study, of a substantive type, and a causal correlational cross-sectional non-experimental design, The Emotional Style Questionnaire (ESQ) was administered and for academic goals the questionnaire of the same name (CMA). The results evidenced the significant incidence of emotional style in the academic goals of university students with 72.1%; because the reason of plausibility of the logistic model (p<0.05) fits well with the data (Deviation with p<0.05).